Association and risk factors analysis of FeNO and CRP in bronchial asthma combined with obstructive sleep apnea - Zhao Yan; Wang Peng Fei; Wang Nai Zhu (Frontiers in Medicine, 2025)
Bronchial asthma (BA) and obstructive sleep apnea (OSA) are chronic disorders of the respiratory system; both diseases are widespread and can cause a decrease in the quality of life. The latter contrasts the airway inflammation and excessive reactivity that define BA, and the intermittent airway obstruction during sleep that defines OSA results in periods of hypoxemia and disruptive breathing. BA appears when children have OSA in addition to other disorders, including night ventilation, breathlessness, and sleep conflicts. Current studies have focused on inflammatory indicators such as the FeNO and CRP in these diseases. FeNO is a measure of eosinophilic airway inflammation, which is usually high in asthma. In, contrast, CRP is a measure of systemic inflammation that is usually high in both forms of asthma. This review paper will focus on FeNO and CRP in connection to the pathophysiology of BA and OSA with further descriptions of how these markers relate to inflammation in both disorders. The review also focuses on how these markers interlink in patients with both diseases and how FeNO and CRP can also reflect the severity of the disease and the effectiveness of the treatments being used. Finally, identifying the interaction between these markers might advance the identification and management of patients with both BA and OSA.